Study on the characteristic of the grounding fault on the cascaded midpoint side of the hybrid cascaded HVDC system - Ren, Yonghao; Sun, Huadong; Wang, Shanshan; Zhao, Bing; Xu, Shiyun; Liu, Min; Lian, Panjie (Frontiers in Energy Research, 2023)
The hybrid cascaded high-voltage direct current (HVDC) system combines the system support capabilities of the modular multilevel converter (MMC) with the capacity of the line-mutated converter’s (LCC’s) advantage of high-power transmission. The HVDC system is among the key elements of a smart grid where artificial intelligence is applied extensively. However, the characteristics of a grounding fault on the cascaded midpoint side of a hybrid cascaded HVDC system remain unclear. This study analyzes fault characteristics and the impact of faults using analytical methods. First, the topology and basic control strategy are presented. The fault response process is then analyzed by dividing systems into the MMC and LCC parts at the inverter side. A separate theoretical analysis is also conducted. In addition, the impacts of faults on HVDC and alternating current (AC) networks are analyzed. Therefore, even after the HVDC system is disabled, the AC network can supply fault currents using an antiparallel diode. The simulation results show that the proposed analysis method is feasible, and the theoretical analysis is correct. The proposed method can provide a theoretical basis for the selection of equipment for HVDC systems and smart grid construction.